A pós-utopia nos versos de Humberto Gessinger (TEL Tempo, Espaço e Linguagem, 2022)
This study is based on the premise that the youth of the Brazilian generation of the 1980s and 1990s question identity, references, ideologies and positions before the social-political framework, situating and reflecting the post-utopian contemporary man, reflections promoted through the essentially poetic language of song lyrics. The objective, therefore, was to investigate how, in the poetic construction of Humberto Gessinger; this collective discourse of the post-utopia resonates. To reach this goal, we selected "Toda forma de Poder", "Revolta de Dandis II", and "Somos quem podemos ser" as base poems, in dialog with others of his authorship. In the ingenuity of Humberto Gessinger's verses, the structural and stylistic elements show themselves as poetic strategies that make explicit and allude to political and social issues, in order to build the ethos of post-utopian indignation of the post 1985 period.KEYWORDS: Humberto Gessinger; poetry-music, post-utopia; 1980s decade.